Prototype Listrik Tenaga Pikohidro (PPT 1.0) untuk Alat Bantu Identifikasi Potensi dan Praktikum Mahasiswa Energi - Masrur Alatas; Ucik Ika Fenti Styana; Dimas Taufiq Ridlo; Fifin Hindarti; Adi Kurniawan (Universitas Proklamasi 45, 2025)
Indonesia's energy needs continue to rise, while its fossil fuel resources are limited. The national energy mix for renewable energy programs is planned to reach 31% by 2030. Indonesia's pico-hydro potential is substantial, found in mountainous areas, rural areas, suburbs, and islands. Potential is also found in primary, secondary, and tertiary irrigation areas, small rivers, waterfalls, pond circulation, and even in rainwater gutters. The research method for identifying potential in the field used a Portable Pico-hydro Turbine (PPT 1.0) with direct testing and student laboratory experiments. The results of the pico-hydro prototype study can be used to identify 26 potential pico-hydro points, which can function as 100-watt street lighting and support student energy laboratory equipment.